2019
DOI: 10.1249/mss.0000000000001981
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Muscle–Tendon Unit Length on Child–Adult Difference in Neuromuscular Fatigue

Abstract: Purpose: The purpose of this study was to compare the development and etiology of neuromuscular fatigue of the knee extensor muscles (KE) at different muscle-tendon unit (MTU) lengths during repeated maximal voluntary isometric contractions (MVIC) between boys and men.Methods: Twenty-two pre-pubertal boys (9-11 years) and 22 men (18-30 years) performed three KE fatigue protocols at short (SHORT), optimal (OPT) and long (LONG) MTU lengths, consisting of repeating 5-s MVIC interspersed with 5-s passive recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 46 publications
2
26
1
Order By: Relevance
“…We hypothesized that the similar fatigue between boys and men with PF muscles could be explained by reduced differences in the torque level of the PF, compared with the KE muscles. This proposition was also sustained by the fact that boys and men performed the same number of repetitions during an intermittent fatigue protocol with KE at short MTU length, where difference in torque level between boys and men is lower than at optimal MTU length (Piponnier et al 2019). However, in the present study, PF MTU length had no effect on differences in the development of the neuromuscular fatigue between boys and men, while it influenced differences in torque level between age groups.…”
Section: Muscle-tendon Unit Length Effect On Difference In Neuromuscular Fatigue Between Boys and Mensupporting
confidence: 61%
See 1 more Smart Citation
“…We hypothesized that the similar fatigue between boys and men with PF muscles could be explained by reduced differences in the torque level of the PF, compared with the KE muscles. This proposition was also sustained by the fact that boys and men performed the same number of repetitions during an intermittent fatigue protocol with KE at short MTU length, where difference in torque level between boys and men is lower than at optimal MTU length (Piponnier et al 2019). However, in the present study, PF MTU length had no effect on differences in the development of the neuromuscular fatigue between boys and men, while it influenced differences in torque level between age groups.…”
Section: Muscle-tendon Unit Length Effect On Difference In Neuromuscular Fatigue Between Boys and Mensupporting
confidence: 61%
“…This postulation is sustained by the statistical analyses conducted by Ratel and collaborators (2015), showing that the development and etiology of the neuromuscular fatigue were not different when the initial torque level was used as co-variate. In addition, our previous results showed that difference in torque levels between children and adults vary as a function of muscle groups (Piponnier et al 2018a) and knee extensors (KE) muscle-tendon unit (MTU) length (Piponnier et al 2019). In these studies, reduced torque level differences between children and adults (i.e.…”
Section: Introductionmentioning
confidence: 95%
“…The lesser fatigue in youths compared to adults following exercise has been shown within a range of exercise modalities with pre-pubertal boys displaying a greater maintenance of peak torque than adults following dynamic maximum isokinetic [ 67 , 73 , 74 , 75 , 76 , 77 ] and isometric [ 65 , 78 , 79 ] actions of the knee extensors and flexors, maximal isometric exercise of the elbow flexors [ 68 ], and isometric exercise of the plantar flexors [ 64 ]. The lower reductions in force-generating capacity following resistance exercise-induced fatigue in youth compared to adults have been shown to occur in conjunction with smaller alterations of neuromuscular properties including sarcolemma excitability (i.e., M-wave amplitude), excitation–contraction coupling (i.e., low-to-high frequency tetanic force ratio or low-frequency fatigue), muscle contractility (i.e., high-frequency torque) and muscle oxygenation [ 63 , 64 , 68 , 71 , 72 , 73 , 78 , 79 , 80 , 81 ]. Conversely, during submaximal isometric RT, differences in fatigue responses including torque and surface electromyography (EMG) have not been observed between children and men [ 82 , 83 ].…”
Section: Neuromuscular and Metabolic Responses To Exercise In Youtmentioning
confidence: 99%
“…The variances in fatigue during exercise may be muscle-dependent as well as being influenced by the muscle-tendon unit (MTU) length. This has been observed during isometric fatiguing actions of the plantar flexor (PF) and knee extensor (KE) muscle groups in which boys fatigued similarly to men with the PF muscles but to a lower extent with the KE muscles than men [ 80 ]. With regards to the MTU length, neuromuscular fatigue at optimal and long MTU lengths are lower in children compared to adults, which are mainly accounted for by central fatigue (i.e., a reduction in drive to the muscle), rather than peripheral fatigue (i.e., failure in muscle contractility and excitation–contraction coupling (E–C).…”
Section: Neuromuscular and Metabolic Responses To Exercise In Youtmentioning
confidence: 99%
See 1 more Smart Citation